Finite Element Analysis to Compare Complete Denture and Implant-Retained Overdentures With Different Attachment Systems - Ricardo Barao, Valentim Adelino [UNESP]; Assunção, Wirley Goncalves [UNESP]; Tabata, Lucas Fernando [UNESP]; Delben, Juliana Aparecida [UNESP]; Gomes, Erica Alves [UNESP]; Sousa, Edson Antonio Capello [UNESP]; Rocha, Eduardo Passos [UNESP] (Lippincott Williams & Wilkins, 2009)
This finite element analysis compared stress distribution on complete dentures and implant-retained overdentures with different attachment systems. Four models of edentulous mandible were constructed: group A (control), complete denture; group B, overdenture retained by 2 splinted implants with bar-clip system; group C, overdenture retained by 2 unsplinted implants with o'ring system; and group D, overdenture retained by 2 splinted implants with bar-clip and 2 distally placed o'ring system. Evaluation was performed on Ansys software, with 100-N vertical load applied on central incisive teeth. The lowest maximum general stress value (in megapascal) was observed in group A (64.305) followed by groups C (119.006), D (258.650), and B (349.873). The same trend occurred it) supporting tissues with the highest stress value for cortical bone. Unsplinted implants associated with the o'ring attachment system showed the lowest maximum stress values among all overdenture groups. Furthermore, o'ring system also improved stress distribution when associated with bar-clip system.
Keywords: Dental implants; complete denture; overdenture; attachment; finite element analysis